Strength and sorption properties of cement bonded composites made from calamus deerratus and laccosperma secundiflorum canes (2012)
"Two layers rattan cement composites were made from Calamus deerratus and Laccosperma secundiflorum particles using cement: sand:rattan mixing ratios of 1:2:0.2 and 1:3:0.2 and calcium chloride (CaCl2) at two levels 0% and 3% (by weight of cement) and subjected to static bending and sorption tests after production. Results showed that rattan-cement mixes had low moduli of rupture, thickness swelling and water absorption rates but high moduli of elasticity and are suitable for low stress out-door applications. While the Calamus composites generally had low strength and high sorption properties than the Laccosperma cement mixes, peeling significantly reduced the strength properties of the Calamus cement composites possibly due to higher presence of cement inhibitors. Addition of CaCl2 significantly enhanced both the strength and sorption properties of composites made from Calamus and Laccosperma particles "